Changes in bone marrow morphology in adults receiving romiplostim for the treatment of thrombocytopenia associated with primary immune thrombocytopenia - Janssens, Ann; Rodeghiero, Francesco; Anderson, David; Chong, Beng H; Boda, Zoltán; Pabinger, Ingrid; Červinek, Libor; Terrell, Deirdra R; Wang, Xuena; Franklin, Janet (Annals of hematology, 2016)
The effects of romiplostim on bone marrow morphology were evaluated in adults with immune thrombocytopenia (ITP). Patients with platelet counts <50 × 10(9)/L, ≥1 prior ITP therapies, and no collagen at baseline received weekly subcutaneous romiplostim starting at 1 μg/kg, adjusted to maintain platelet counts between 50 and 200 × 10(9)/L. Biopsies were scheduled after 1, 2, or 3 years of romiplostim (cohorts 1, 2, and 3, respectively). Irrespective of scheduled time, biopsies were performed earlier if patients discontinued or failed to achieve/maintain a response to romiplostim. Reticulin (silver stain) and collagen (trichrome stain) were graded by two hematopathologists using the modified Bauermeister scale (0-4). Of 169 patients, 131 had evaluable biopsies; 9/131 (6.9 %) had increases of ≥2 grades on the modified Bauermeister scale (cohort 1: 0/34; cohort 2: 2/39; cohort 3: 7/58), including two with collagen. Three of the nine patients had follow-up biopsies, including one patient with collagen; changes were reversible after romiplostim discontinuation. Of the nine patients, one had neutropenia detected by laboratory test and two had adverse events of anemia, both non-serious and not treatment-related. By actual exposure (as some biopsies did not occur as scheduled), the number of patients with grade increases ≥2 were year 1: 3/41, year 2: 1/38, year 3: 5/52. Twenty-four patients sustained platelet counts ≥50 × 10(9)/L for ≥6 months with no ITP medications after discontinuing romiplostim, i.e., they entered clinical remission of their ITP. In conclusion, in patients with ITP receiving romiplostim, bone marrow changes were observed in a small proportion of patients.ClinicalTrials.gov identifier: NCT#00907478.
Keywords: dospělí; Purpura, Thrombocytopenic, Idiopathic; Thrombopoietin; Female; Thrombopoietin (TPO); Adult; výsledek terapie; ženské pohlaví; Recombinant Fusion Proteins; thrombopoetin; Collagen; rekombinantní fúzní proteiny; lidé; Bone Marrow; kolagen; idiopatická trombocytopenická purpura; Treatment Outcome; počet trombocytů; kohortové studie; Receptors, Fc; Cohort Studies; Platelet Count; kostní dřeň; prospektivní studie; Male; Aged; Prospective Studies; Immune thrombocytopenia (ITP); Reticulin; Platelet; receptory Fc; lidé středního věku; retikulin; Bone marrow; senioři; mužské pohlaví; Middle Aged; Humans